The peculiarities of spectra in high power 970 laser diodes. (August 2016) - Bezotosnyi, V V; Krokhin, O N; Oleshchenko, V A; Pevtsov, V F; Popov, Yu M; Cheshev, E A
Abstract: We present the results of optical power, total efficiency and spectra of CW laser diodes emitting at wavelength 970 nm. Total efficiency in maximum 72% was measured and reliable operation at 15 W CW was achieved. At the base of measured CW spectral parameters in wide range of pump currents we discuss the possible reasons of observed features in dependences of spectral envelope, spectral maximum and spectral half-width against pumping current.